Urinary Purine Derivatives Excretion as a Method for Estimation of Rumen Microbial Protein Production in Swamp Buffaloes and Zebu Cattle - Pimpa, Opart (2002)
Prediction equations based on urinary purine derivatives (PD) excretion rate as an index to predict rumen microbial protein production have been developed for European cattle and sheep. However, there is evidence to suggest that those equations may not be applicable directly to tropical swamp buffaloes (Bubalus bubalis) and zebu cattle (Bos indicus). To establish similar equations for the above two species of ruminant, five studies were conducted. In the first study, endogenous PD excretion rate determined by fasting procedure for swamp buffaloes and the Malaysian indegenous KK. cattle (zebu cattle) were 199 and 300 Ilmol/kgO.75 /day, respectively. Urinary PD excretion rate per kg digestible organic matter intake (DOMI) for buffaloes (8.19 mmol/kg DOMI) was significantly lower than that for KK. cattle (15.45 mmol/kg DOMI). The second study examined the relationship between daily urinary PD excretion (Y, mmol) and exogenous purine bases (PB) supply via duodenal infusion (X, mmol/day). The relationship obtained were Y = O. I 2X+ 12.78 (r2= 0.45) for buffaloes and Y = 0.85X + 7.15 (r2= 0.62) for KK. cattle, suggesting that 12% and 85% of the supplied exogenous purine were excreted in the urine of buffaloes and zebu cattle, respectively. In the third study, labelled [8_14C] uric acid marker was used to test the hypothesis that the lower recovery rate of urinary PD in swamp buffaloes was due to their higher recycling of plasma PD as compared to KK cattle. The averaged non-renal PD loss of plasma PD for swamp buffaloes and KK cattle did not differ significantly.